Robustness and energy efficiency – a logical multi‐topology scheme for time‐varying traffic in IP networks. Issue 3 (1st May 2015) - Wang, Jin; Wang, Sheng; Xu, Shizhong
Abstract : This study deals with a strategy to save energy in an Internet protocol (IP) network allowing different subsets of IP links to be put in the sleep mode during different traffic periods. The proposed solution involves a three‐phase algorithm. In the first phase, time‐varying critical traffic matrices from a large collection of real traffic matrices are obtained. In the second phase, a local search heuristic algorithm is utilised that is based on the link weight setting for the energy‐saving optimisation corresponding to the critical traffic matrices. In the last phase, the real traffic flows are routed with the corresponding logical topologies. According to the performance studies that are conducted in a synthetic network and actual IP networks, this approach can achieve significantly improved energy efficiency while certain max link utilisation performance specifications and requirements are satisfied.